ACL Roof Impingement Revisited: Does the Independent Femoral Drilling Technique Avoid Roof Impingement With Anteriorly Placed Tibial Tunnels?. Issue 5 (18th May 2017) - Tanksley, John A.; Werner, Brian C.; Conte, Evan J.; Lustenberger, David P.; Burrus, M. Tyrrell; Brockmeier, Stephen F.; Gwathmey, F. Winston; Miller, Mark D.
Background: Anatomic femoral tunnel placement for single-bundle anterior cruciate ligament (ACL) reconstruction is now well accepted. The ideal location for the tibial tunnel has not been studied extensively, although some biomechanical and clinical studies suggest that placement of the tibial tunnel in the anterior part of the ACL tibial attachment site may be desirable. However, the concern for intercondylar roof impingement has tempered enthusiasm for anterior tibial tunnel placement. Purpose: To compare the potential for intercondylar roof impingement of ACL grafts with anteriorly positioned tibial tunnels after either transtibial (TT) or independent femoral (IF) tunnel drilling. Study Design: Controlled laboratory study. Methods: Twelve fresh-frozen cadaver knees were randomized to either a TT or IF drilling technique. Tibial guide pins were drilled in the anterior third of the native ACL tibial attachment site after debridement. All efforts were made to drill the femoral tunnel anatomically in the center of the attachment site, and the surrogate ACL graft was visualized using 3-dimensional computed tomography. Reformatting was used to evaluate for roof impingement. Tunnel dimensions, knee flexion angles, and intra-articular sagittal graft angles were also measured. The Impingement Review Index (IRI) was used to evaluate for graft impingement. Results: Two grafts (2/6, 33.3%) in the TT group impinged upon the intercondylar roof and demonstrated angular deformity (IRI type 1). No grafts in the IF group impinged, although 2 of 6 (66.7%) IF grafts touched the roof without deformation (IRI type 2). The presence or absence of impingement was not statistically significant. The mean sagittal tibial tunnel guide pin position prior to drilling was 27.6% of the sagittal diameter of the tibia (range, 22%-33.9%). However, computed tomography performed postdrilling detected substantial posterior enlargement in 2 TT specimens. A significant difference in the sagittal graft angle was noted between the 2 groups. TT grafts were more vertical, leading to angular convergence with the roof, whereas IF grafts were more horizontal and universally diverged from the roof. Conclusion: The IF technique had no specimens with roof impingement despite an anterior tibial tunnel position, likely due to a more horizontal graft trajectory and anatomic placement of the ACL femoral tunnel. Roof impingement remains a concern after TT ACL reconstruction in the setting of anterior tibial tunnel placement, although statistical significance was not found. Future clinical studies are planned to develop better recommendations for ACL tibial tunnel placement. Clinical Relevance: Graft impingement due to excessively anterior tibial tunnel placement using a TT drilling technique has been previously demonstrated; however, this may not be a concern when using an IF tunnel drilling technique. There may also be biomechanical advantages to a more anterior tibial tunnel in IF tunnel ACL reconstruction.